Renal dysfunction in patients with cirrhosis: Where do we stand? - Pipili, Chrysoula (Baishideng Publishing Group Inc, 2014)
Patients with cirrhosis and renal failure are high-risk patients who can hardly be grouped to form precise instructions for diagnosis and treatment. When it comes to evaluate renal function in patients with cirrhosis, determination of acute kidney injury (AKI), chronic kidney disease (CKD) or AKI on CKD should be made. First it should be excluded the prerenal causes of AKI. All cirrhotic patients should undergo renal ultrasound for measurement of renal resistive index in every stage of liver dysfunction and urine microscopy for differentiation of all causes of AKI. If there is history of dehydration on the ground of normal renal ultrasound and urine microscopy the diuretics should be withdrawn and plasma volume expansion should be tried with albumin. If the patient does not respond, the correct diagnosis is HRS. In case there is recent use of nephrotoxic agents or contrast media and examination shows shock, granular cast in urinary sediment and proteinuria above 0.5 g daily, acute tubular necrosis is the prominent diagnosis. Renal biopsy should be performed when glomerular filtration rate is between 30-60 mL/min and there are signs of parenchymal renal disease. The acute renal function is preferable to be assessed with modified AKIN. Patients with AKIN stage 1 and serum creatinine ≥ 1.5 mg/dL should be at close surveillance. Management options include hemodynamic monitoring and management of fluid balance and infections, potentially driving to HRS. Terlipressin is the treatment of choice in case of established HRS, administered until there are signs of improvement, but not more than two weeks. Midodrine is the alternative for therapy continuation or when terlipressin is unavailable. Norepinephrine has shown similar effect with terlipressin in patients being in Intensive Care Unit, but with much lower cost than that of terlipressin. If the patient meets the requirements for transplantation, dialysis and transjugular intrahepatic portosystemic shunt are the bridging therapies to keep the transplant candidate in the best clinical status. The present review clarifies the latest therapeutic modalities and the proposed recommendations and algorithms in order to be applied in clinical practice.